Endoscopic vacuum therapy for anastomotic leakage after upper gastrointestinal surgery - Pattynama, Lisanne M. D.; Pouw, Roos E.; Henegouwen, Mark I. van Berge; Daams, Freek; Gisbertz, Suzanne S.; Bergman, Jacques J. G. H. M.; Eshuis, Wietse J. (Endoscopy, 2023)
Background Recently, endoscopic vacuum therapy (EVT) was introduced as treatment for anastomotic leakage after upper gastrointestinal (GI) surgery. The aim of this study was to describe the initial experience with EVT for anastomotic leakage after upper GI surgery in a tertiary referral center.Methods Patients treated with EVT for anastomotic leakage after upper GI surgery were included retrospectively (January 2018–June 2021) and prospectively (June 2021–October 2021). The primary end point was the EVT success rate. Secondary end points included mortality and adverse events.Results 38 patients were included (31 men; mean age 66 years): 27 had undergone an esophagectomy with gastric conduit reconstruction and 11 a total gastrectomy with esophagojejunal anastomosis. EVT was successful in 28 patients (74 %, 95 %CI 57 %–87 %). In 10 patients, EVT failed: deceased owing to radiation pneumonitis (n = 1), EVT-associated complications (n = 2), and defect closure not achieved (n = 7). Mean duration of successful EVT was 33 days, with a median of six EVT-related endoscopies. Median hospital stay was 45 days.Conclusion This initial experience with EVT for anastomotic leakage after upper GI surgery demonstrated a success rate of 74 %. EVT is a promising therapy that could prevent further major surgery. More experience with the technique and its indications will likely improve success rates in the future.